The Economic Feasibility and Sensitivity Analysis of Carbon Capture and Utilization in Indonesian Coal-Fired Power Plants - Anggoro, Yohanes Dwi; Priambodo, Dedy; Suparman, Suparman; Susiati, Heni; Sriyana, Sriyana; Birmano, Moch. Djoko; Irawan, Dimas; Fepriadi, Fepriadi; Aryanto, Agus (International Journal of Energy Economics and Policy, 2025)
This study explores the economic feasibility of implementing Carbon Capture and Storage (CCS) and Carbon Capture, Utilization, and Storage (CCUS) technologies in Indonesian coal-fired power plants (CFPPs). CCS/CCUS is seen as crucial to achieving net-zero emissions by capturing carbon dioxide (CO2) and either storing it underground or utilizing it for enhanced oil recovery (EOR). However, the application of these technologies results in a significant increase in the Levelized Cost of Electricity (LCOE) due to higher capital and operational expenses. The study compares CFPPs without CCS, with CCS, and with CCUS, analyzing key financial indicators like Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR). Additionally, sensitivity analyses on carbon tax, electricity prices, and EOR benefit-sharing are conducted to assess the conditions under which these technologies become financially viable. The findings suggest that while CCS technology is economically challenging, CCUS, particularly when integrated with EOR, shows better economic performance. For Indonesia to achieve net-zero targets, a carbon tax of at least 107.3/ton CO2 and electricity prices above 0.18/kWh are recommended to make CCUS economically competitive.